Erratum: Spatio-temporal propagation of COVID-19 pandemics. (13th October 2020) - Gross, Bnaya; Zheng, Zhiguo; Liu, Shiyan; Chen, Xiaoqi; Sela, Alon; Li, Jianxin; Li, Daqing; Havlin, Shlomo
Abstract: Original article: EPL, 131 (2020) 58003 .